Gastro-Intestinal Complaints Related to Various Eating Behaviors - Burkert, Nathalie Tatjana; Großschädl, Franziska; Muckenhuber, Johanna; Rásky, Éva; Stronegger, Willibald Julius; Freidl, Wolfgang (Journal of Nutritional Therapeutics, 2012)
Background: Many studies report a beneficial health effect as well as a lower mortality rate for individuals following diets containing lots of fruits and vegetables. Results of studies on abdominal, and colon diseases are, however, inconsistent. Therefore, the aim of our study was to analyze differences between various eating behaviors and the incidence of gastro-intestinal complaints. Methods: The sample used for this study was taken from the Austrian Health Interview Survey ATHIS 2006/07 (N=14 318). Logistic regressions were calculated controlling for age, BMI, and physical activity to analyze differences regarding the incidence of gastric or intestinal ulcer, abdominal pain, and specific medication taken due to these complaints. Results: A lacto-/ovo-, as well as a semi-vegetarian diet is associated with a higher risk for gastrointestinal complaints. The odds ratio for gastric or intestinal ulcer, and the intake of specific medication is significantly higher for these diets. Conclusion: A carnivorous diet containing also lots of fruits and vegetables is recommended to avoid abdominal complaints. Furthermore, public health programs are needed in order to reduce the health risk due to nutritional factors.